DIAGNOSIS OF TRAUMATIC BRAIN INJURY (TBI) - Saboya, Maria Fernanda Leite; de Souza, Jaiara; Toledo, Rodolfo Ricardo; Reges, Flávio Henrique do Nascimento; de Brito, Yasmin das Chagas; de Oliveira, Rafael Augusto (Seven Editora, 2026)
Traumatic brain injury (TBI) is one of the leading global causes of mortality and disability, classically classified by the Glasgow Coma Scale (GCS). Accurate and rapid diagnosis is vital to mitigate secondary damage, such as ischemia, cerebral edema, and intracranial hypertension (ICH). This study is characterized as a narrative literature review, structured to synthesize contemporary evidence on TBI diagnostic protocols, with articles published between 2021 and 2025. The results confirm non-contrast computed tomography (CT) of the head as the initial gold standard for detecting acute injuries, but highlight the diagnostic evolution towards a multimodal and longitudinal approach. Notable advances include the validation of blood biomarkers (GFAP, UCH-L1) for screening patients with mild TBI and the increasing use of fast magnetic resonance imaging (MRI) sequences in pediatrics for visualization of diffuse axonal injury (DAI). In the context of intensive care, invasive monitoring of intracranial pressure (ICP) and brain tissue oxygen pressure (PbtO₂) is crucial. It is concluded that modern TBI diagnosis should combine clinical assessment (GCS, pupillary reactivity), the speed of CT, the sensitivity of biomarkers, and the precision of intracranial monitoring to ensure survival and quality of life, extending long-term to track complications such as hypopituitarism and systemic inflammation.